Inhibition of Fatty Acid–Binding Protein 4 Attenuated Kidney Fibrosis by Mediating Macrophage-to-Myofibroblast Transition - Feng, Yanhuan; Guo, Fan; Xia, Zijing; Liu, Jing; Mai, Hongxia; Liang, Yan; Zhu, Guonian; Li, Yanping; Bai, Lin; Li, Lingzhi; Huang, Rongshuang; Shi, Min; et al. (Frontiers in Immunology, 2020)
The macrophage-to-myofibroblast transition (MMT) process is an important pathway that contributing to renal interstitial fibrosis (RIF). Fatty acid-binding protein 4 (FABP4) deteriorated RIF via promoting inflammation in obstructive nephropathy. However, the clinical significance of FABP4 in fibrotic kidney disease remains to be determined and little is known of the FABP4 signaling in MMT. Biopsy specimens of chronic kidney disease patients and kidneys subjected to unilateral ureteral obstruction (UUO) of FABP4-deficient mice or FABP4 inhibitor-treated mice were collected for the investigation of FABP4 mediating MMT of RIF. We conducted kidney RNA-seq transcriptomes and TGF-β1-induced bone marrow-derived macrophages assays to determine the mechanisms of FABP4. We found that FABP4 expression correlated with RIF in biopsy specimens and the injured kidneys of UUO mice where FABP4 was co-expressed with MMT cells. In UUO mice, FABP4 deficiency and a highly selective FABP4 inhibitor BMS309403 treatment both suppressed RIF. FABP4 ablation also attenuated the UUO-induced number of MMT cells and serum amyloid A1 (Saa1) expression. The siRNA-mediated Saa1 knockdown decreased the number of MMT cells in vitro. In conclusion, FABP4 is an important factor contributing to RIF by mediating MMT, and genetic/pharmacological inhibition of FABP4 provides a novel approach for the treatment of kidney fibrosis.